Prevalence of hypertensive disorders of pregnancy at or beyond 39 weeks gestational age and associated maternal complications - Elizabeth Fronek; Summer Martins; Stephen Contag (Taylor & Francis Group, 2023)
Objective Estimate the prevalence of hypertensive disorder of pregnancy (HDP) at term, define population characteristics, and calculate adverse maternal outcomes. Methods Retrospective study. Results We included 4,702,468 pregnancies. HDP increased linearly from 4.5% (2014) to 6.0% (2018). HDP was more frequent among black (PR 1.19), obese (PR 2.31 to 3.70), with gestational (PR 1.87) or pregestational diabetes (PR 2.16). Increased transfusion (PR 2.52), intensive care unit admission (PR 3.38), and unplanned hysterectomy (PR 1.78) with HDP.  Conclusion Our study quantifies the increased risks for maternal and neonatal complications related to the development of HDP at or beyond 39 weeks among nulliparous women.